REPRESENTATION OR MISREPRESENTATION OF AUTISTIC AGENCY? MULTIMODAL LITERACY ANALYSIS OF MAKAYLA’S VOICE - Sari, Artanti Puspita (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
While media portrayals of autism have been widely studied, limited research has examined how the agency of non-speaking autistic individuals is constructed through multimodal storytelling and mediated communication. This study examines how nonverbal autistic agency is portrayed in the Netflix documentary